From common biomass materials to high-performance tissue engineering scaffold: Biomimetic preparation, properties characterization, in vitro and in vivo evaluations - Zongpu Xu; Fang He; Jing Yu; Zhangze Yang; Yu Zhu; Rong Liao; Ruyin Lyu; Mei Yang; Liangjun Zhu; Mingying Yang (Journal of Bioresources and Bioproducts, 2024)
Converting common biomass materials to high-performance biomedical products could not only reduce the environmental pressure associated with the large-scale use of synthetic materials, but also increase the economic value. Chitosan as a very promising candidate has drawn considerable attention owing to its abundant sources and remarkable bioactivities. However, pure chitosan materials usually exhibit insufficient mechanical properties and excessive swelling ratio, which seriously affected their in vivo stability and integrity when applied as tissue engineering scaffolds. Thus, simultaneously improving the mechanical strength and biological compatibility of pure chitosan (CS) scaffolds becomes very important. Here, inspired by the fiber-reinforced construction of natural extracellular matrix and the porous structure of cancellous bone, we built silk microfibers/chitosan composite scaffolds via ice-templating technique. This biomimetic strategy achieved 500% of mechanical improvement to pure chitosan, and meanwhile still maintaining high porosity (> 87%). In addition, the increased roughness of chitosan pore walls by embedded silk microfibers significantly promoted cell adhesion and proliferation. More importantly, after subcutaneous implantation in mice for four weeks, the composite scaffold showed greater structural integrity, as well as better collagenation, angiogenesis, and osteogenesis abilities, suggesting its great potential in biomedicine.